MORALITAS TOKOH MINKE DALAM ROMAN TETRALOGI BURU KARYA PRAMOEDYA ANANTA TOER - Wangunati, Gaudensia; Effendy, Chairil; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is based on the writer's desire to find the minke character of Minke in Roman Tetralogy of Buru by Pramoedya Ananta Toer. The morality depicted in the Tetralogy of Buru is the morality of the Minke character. The general problem described in this study is